AI Power, Resistance, and Cultural Hegemony in The Golden Legend: A Foucauldian and Gramscian Analysis - Anam Javed; Daryoosh Hayati (WISE Pendidikan Indonesia, 2026)
This study examines how power, resistance, and cultural hegemony are represented in Nadeem Aslam’s The Golden Legend, with particular attention to the discursive construction of religious minority identity, gendered vulnerability, and ideological belonging in a postcolonial society. The study responds to the need for a more integrated reading of the novel, since previous scholarship has generally examined religious intolerance, minority representation, gendered subjectivity, nationalism, or Foucauldian surveillance as relatively separate concerns. Using a qualitative, interpretive, and non-empirical textual approach, the study applies Foucault’s concepts of disciplinary power, subjectification, discourse, and resistance, complemented by Gramsci’s theory of cultural hegemony. The analysis was conducted through close reading, deductive thematic coding, and critical discourse interpretation of selected narrative passages, character interactions, and representations of institutional authority. The findings show that power in the novel operates through religious authority, military pressure, patriarchal norms, communal surveillance, legal fear, and ideological consent. Marginalized characters internalize fear through silence, concealment, and self-regulation, yet they also resist through moral defiance, ethical refusal, compassion, memory, and identity reconstruction. The study concludes that The Golden Legend is not merely a narrative of oppression but a literary representation of how language, ideology, and identity become central sites where domination is produced, normalized, contested, and transformed. This study contributes an integrated Foucauldian-Gramscian framework for analyzing discourse, power, and resistance in postcolonial literary texts.